Strategic Considerations for Customer Relationship Management in the Telecommunications Industry - Brown, Benjamin Philip Edward (2007)
This dissertation explores the concept of Customer Relationship Management and considers the various strands of strategic consideration that affect how firms in the telecommunications industry conduct business with their customers. Included is a literature review, which attempts to introduce and synthesise conceptual CRM constructs, followed by a Methodology and subsequent case-study analysis of Vodafone. The Methodology ensures that the techniques employed are adequately accounted for. The intention of this is to deem the dissertation as well-rounded, thorough and insightful as possible. The Vodafone case-study utilises real industry data to apply theory in a practical business environment. This allows the project to reach a summary at the end where each strategic consideration is valued on the basis of its perceived contribution.